"Her story was complex": A Twine workshop for ten- to twelve-year-old girls. (September 2016) - Tran, Kelly M.
In this study, I discuss the need to increase girls' involvement with game design due to the numerous benefits that engaging in this practice might have. In particular, I discuss the tool Twine, an accessible and relatively easy-to-use platform for creating text-based games. I provide an overview of the tool and its potential benefits for learning, including traditional and digital literacy skills. I present the findings from an after-school workshop in which I led a small group of ten- to twelve-year old girls in designing their own games. Finally, the ways in which the girls engaged with the tool and the workshop, and the implications for literacy and education, are discussed.